Cancer- A disease we should care about - Shah Sumaya Jan; Saleem Sheikh Mohd (International Journal of Medical Research and Review, 2018)
Cancer is primarily an illness of aging. It is being postulated that the Cancer cells use stop inhibitors to cover the body destructive mechanisms and seem to be healthy cells before such destructive mechanisms to flee destruction. Researchers have created artificial promoters that contain DNA sequences which initiate organic phenomenon solely in cancerous cells. A few individuals inherit faulty genes from their ancestors that place them at a higher risk of developing diseases like cancer.